2010
DOI: 10.1093/chemse/bjq070
|View full text |Cite
|
Sign up to set email alerts
|

Taste Function in Mice with a Targeted Mutation of the Pkd1l3 Gene

Abstract: Recent studies, both in vitro and in vivo, have suggested the involvement of the polycystic kidney disease-1 and -2 like genes, Pkd1l3 and Pkd2l1, in acid taste transduction. In mice, disruption of taste cells expressing PKD2L1 eliminates gustatory neural responses to acids. However, no previous data exist on taste responses in the absence of PKD1L3 or on behavioral responses in mice lacking either of these proteins. In order to assess the function of PKD1L3, we genetically engineered mice with a targeted muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 57 publications
1
60
0
Order By: Relevance
“…Notably, although an initial report showed that the PKD2L1/ PKD1L3 heteromer was activated by exposure to solutions of low pH (pH <3) (14), subsequent reports show that activation occurs at a delay upon removal of the acid (17,18). Moreover, a recent study of mice carrying a targeted deletion of PKD1L3 found no significant deficits in behavioral or nerve responses to sour stimuli (19).…”
mentioning
confidence: 99%
“…Notably, although an initial report showed that the PKD2L1/ PKD1L3 heteromer was activated by exposure to solutions of low pH (pH <3) (14), subsequent reports show that activation occurs at a delay upon removal of the acid (17,18). Moreover, a recent study of mice carrying a targeted deletion of PKD1L3 found no significant deficits in behavioral or nerve responses to sour stimuli (19).…”
mentioning
confidence: 99%
“…In contrast, the CT nerve responses in Pkd1l3 KO mice and glossopharyngeal (GL) nerve responses in single-and double-KO (both Pkd1l3 and Pkd2l1) mice are comparable to the responses observed in wild-type mice. 26,31) These results indicate that Pkd1l3 is not required for acid detection in TRCs, Pkd2l1 is required at least in part for acid sensing in TRCs innervated by the CT nerve (the FuP and palate TRCs), and that there is a different soursensing mechanism for TRCs innervated predominantly by the GL nerve (the FoP and CvP TRCs).…”
Section: Molecular Basis Of Acid Sensingmentioning
confidence: 92%
“…All methods of mouse handling were approved by the University of Southern California Institutional Animal Care and Use Committee. Mouse strains Pkd2l1-YFP, Pkd1l3 −/− were previously described (14,16). Mouse strains Kcnj2 fl/fl , Pkd2l1-Cre are described in SI Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Both strong acids, such as hydrochloric acid, and weak acids, such as acetic or citric acid, produce a sour sensation in humans and evoke sensory responses in nerve recordings in a variety of model organisms, including rat, mouse, and hamster (4)(5)(6)(7). A number of molecules have been proposed to transduce sour taste, most recently the ion channel PKD2L1/PKD1L3 (8)(9)(10)(11)(12), but their role in taste transduction remains unclear as subsequent studies using knockout mouse strains have failed to identify significant effects on sour taste (13)(14)(15). Nonetheless, the Pkd2l1 gene serves as a useful marker for sour taste cells (also designated type III cells), which account for ∼10% of the ∼50-100 taste cells found in each taste bud (1,9,11,16,17).…”
mentioning
confidence: 99%